Effect of actual and accelerated ageing on microstructure evolution and mechanical properties of a 2024-T351 aluminium alloy. (February 2018) - Prudhomme, M.; Billy, F.; Alexis, J.; Benoit, G.; Hamon, F.; Larignon, C.; Odemer, G.; Blanc, C.; Hénaff, G.
Highlights: AA 2024 from a decommissioned aircraft and an artificially aged alloy are studied. Their microstructure (SEM, TEM) and mechanical performances are compared. Electrical conductivity measurements were helpful in studying the aging of AA 2024. Similar results for an end-of-life material and a material aged for 55 h at 150 °C). More significant changes can be anticipated for longer exposures (177 h at 150 °C). Abstract: This paper presents an investigation on the effects of ageing on the microstructure and the corresponding physical and mechanical properties of a 2024 aluminium alloy used in a civil transport aircraft wing structure in order to assess the residual resistance of the end of a service life. More precisely, heat treatments are applied in order to simulate thermal ageing actually endured by the structure during service. The results of characterisation of microstructural, physical and mechanical properties are compared not only to the data obtained on a pristine alloy, but also to the results obtained on coupons of a similar alloy coming from the teardown of an A320 aircraft using the same experimental procedure. The main findings are that, during a service life, no significant modification in fatigue resistance is noticed despite of changes in the precipitation structure.